The Implementation of Geographic Information System for Agricultural Commodities Data Inventory and Land Condition Information in Kudus Regency - Zed Nahdi, Hendy Hendro HS, Hadi Supriyo, Solekhan (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2014)
ABSTRACTIndonesia as an agricultural country needs to ensure the provision of sustainable agricultural land as the main source of income for the majority of its people by fostering the implementation of the principles of efficiency, sustainability, and self-reliance as well as environmentally sound in agricultural land-use. On the other hand, the high population growth of the country (1.4 to 1.5% per year) as well as the economic and industrial development resulted in the degradation and conversion of agricultural lands that hamper the carrying capacity nationally in maintaining independence and food security.Based on this background, system and methodology developed land suitability mapping using spatial and temporal approach. The goals to be achieved is, first of agricultural land suitability analysis is based on the type of agricultural commodities and climate information, both the alignment evaluation of agricultural land use and spatial planning of the area, the third degradation analysis and mapping of agricultural areas based on data for 1990-2010, the four evaluation Spatial Plan (Spatial), and fifth strategies and policies appropriate to the land use for sustainable agriculture and backup. The methods used in this study include descriptive survey, analysis of spatial and temporal data using statistics G*. Range of values used for the classification of documents using agroecological zone guidelines. Keywords: modeling, mapping, spatial, temporal, G * statistic.